Design of Automatic Watering System Prototype with Arduino-Based Soil Moisture Sensor for Strawberry Plants (Fragaria Ananassa) - Ratika Sekar Ajeng Ananingtyas; Ragil Ellang Sakti; Muhammad Helmi Hakim; Rizka Rizqi Robby; Rachmadania Akbarita (Journal of Development Research, 2023)
Automatic water management using an Arduino-based humidity sensor as a microcontroller provides practicality in strawberry cultivation, especially in high temperature areas such as in Blitar City. The purpose of this research is to design and test a automatic watering system prototype with an arduino-based soil moisture sensor for strawberry plants (fragaria ananassa). In this study, the method used was designing a prototype automatic watering system with an arduino-based soil moisture sensor for strawberry plants (fragaria ananassa) according to the design so that the prototype could work properly and testing the prototype for strawberry plants (fragaria ananassa) to get moisture data and the right time for giving water every certain period of time. The research activities were carried out in 4 stages including the needs analysis stage, the prototype design stage, the test and evaluation stage, and the final product stage. From the results of product design and development, it was found that the soil moisture sensor, arduino and water pump work according to the input or command.